Respecting the Patient's Choice: A Case of Possible Drug-Induced Parkinsonism - Megan R. Undeberg; Kimberly C. McKeirnan; David Easley (MDPI AG, 2022)
This report describes a case of likely drug-induced Parkinsonism (DIP) identified by the pharmacist. A 54-year-old female patient was referred by a physician to the pharmacist in a rural, integrated care team for a comprehensive medication review (CMR) to address the patient's concerns of possible Parkinson's disease (PD). While PD may occur over the progression of age, medications that affect dopamine transport can also cause DIP, a secondary form of Parkinson's disease. Although PD and DIP may be clinically indistinguishable, differentiation may be possible by reviewing a patient's medication history for any potential causative drugs correlating to the timeline of the onset of symptoms. In this case, the pharmacist reviewed the medication profile and identified medications that could be responsible for causing DIP, specifically bupropion. The pharmacist suggested discontinuing bupropion and identifying another option for treating depression. The patient appreciated the suggestion and education, but ultimately preferred continuing her bupropion therapy instead of discontinuing therapy or changing to an alternative agent. At a follow-up meeting with the pharmacist, not only was the patient still experiencing tremors despite taking carbidopa/levodopa, but additional medications known to be potential inducers of tremors were added to her regimen. Although the pharmacist repeatedly discussed DIP with the patient and believed stopping bupropion would determine whether her Parkinsonism was PD or DIP, ultimately the patient continued taking bupropion because of concerns related to depression severity and the impact on her well-being. The patient's wishes were respected.